Agronomic biofortification with selenium in tomato crops (Solanum lycopersicon L. Mill) - Rahim, Foroughbakhch Pournavab; Rocio, Castillo Godina; Adalberto, Benavides Mendoza; Lidia Rosaura, Salas Cruz; Maginot, Ngangyo Heya (Multidisciplinary Digital Publishing Institute, 2020)
Biofortification aims to increase the concentration of bioavailable elements in crops, to increase their nutritional quality. Selenium is a trace element of great impact on the antioxidant metabolism of plants and its accumulation is poor in species such as Solanum lycopersicon, so adding it is part of biofortification programs. The present work analyzes the capacity of sodium selenite (Na2SeO3) to increase the concentration of Selenium in tomatoes plants and fruits. For this, three treatments were applied (0, 2, and 5 mg L−1 of sodium selenite) using irrigation water as a vehicle. 40 days after transplanting, the accumulation of selenium and macronutrients in leaves, stems, and fruits was quantified, as well as their impact on tomato plant productivity. Agronomic variables such as height (cm), diameter (mm) of stems, number and weight (g) of fruits produced were determined. The results were analyzed by ANOVA and later, a Tukey mean comparison test was performed. An increase in the accumulation of Se was observed, being up to 53% in the fruits under the 5 mg L−1 treatment compared to the control. However, this increase did not have a noticeable impact on macronutrient content and tomato yield, but rather, contributed to the improvement of the nutritional quality of the tomato.